Academic Development, Teaching Approach, and Student Learning: Professors’ Perspectives at a University in Mozambique (Global Journal of Human-Social Science, 2024)
This article reports on a study on the interconnectedness of academic development and academics approaches to teaching and student learning This study was based on qualitative interviews with 10 professors at a university in Mozambique The results of the study show that participants understand the idea of good teaching in higher education in different ways influenced by a wide variety of factors linked to an educator s background professional development teaching philosophy and understanding of the classroom environment These elements influence how instructors develop their classroom teaching and how student concerns are considered However the impetus for changing towards a more student-centred learning approach was discussed whereby institutional conditions and the motivation for improvement move in opposite directions Hence there is more of a call for improving the quality of teaching and less effort towards ensuring that those implementing it have the right tools and motivation
Keywords: academic development; teaching approach; student learning; student-centred learning